Effects of Intraventricular Methotrexate on Neuronal Injury and Gene Expression in a Rat Model: Findings From an Exploratory Study. (October 2016) - Moore, Ida M. (Ki); Merkle, Carrie J.; Byrne, Howard; Ross, Adam; Hawkins, Ashley M.; Ameli, Sara S.; Montgomery, David W.
Central nervous system (CNS)-directed treatment for acute lymphoblastic leukemia, used to prevent disease recurrence in the brain, is essential for survival. Systemic and intrathecal methotrexate, commonly used for CNS-directed treatment, have been associated with cognitive problems during and after treatment. The cortex, hippocampus, and caudate putamen, important brain regions for learning and memory, may be involved in methotrexate-induced brain injury. Objectives of this study were to (1) quantify neuronal degeneration in selected regions of the cortex, hippocampus, and caudate putamen and (2) measure changes in the expression of genes with known roles in oxidant defense, apoptosis/inflammation, and protection from injury. Male Sprague Dawley rats were administered 2 or 4 mg/kg of methotrexate diluted in artificial cerebrospinal fluid (aCSF) or aCSF only into the left cerebral lateral ventricle. Gene expression changes were measured using customized reverse transcription (RT) 2 polymerase chain reaction arrays. The greatest percentage of degenerating neurons in methotrexate-treated animals was in the medial region of the cortex; percentage of degenerating neurons in the dentate gyrus and cornu ammonis 3 regions of the hippocampus was also greater in rats treated with methotrexate compared to perfusion and vehicle controls. There was a greater percentage of degenerating neurons in the inferior cortex of control versus methotrexate-treated animals. Eight genes involved in protection from injury, oxidant defense, and apoptosis/inflammation were significantly downregulated in different brain regions of methotrexate-treated rats. To our knowledge, this is the first study to investigate methotrexate-induced injury in selected brain regions and gene expression changes using a rat model of intraventricular drug administration.